2015
DOI: 10.1039/c5ta02432c
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous core–shell NiCo2S4 nanostructures supported on nickel foam for supercapacitors

Abstract: Homogeneous core–shell NiCo2S4 nanostructures supported on nickel can be applied as a high-performance supercapacitor electrode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
154
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 437 publications
(169 citation statements)
references
References 46 publications
7
154
1
1
Order By: Relevance
“…4a. The peaks at 169.7, 781.7 and 855.07 eV, corresponds to S 2p, Co 2p and Ni 2p spectrums, respectively, indicating the existence of S, Co and Ni elements in the as-synthesized sample [19]. Figure 4b shows Co 2p spectrum, the Gaussian fitted peaks around binding energy of 781.931 and 797.677 eV shows the existence of Co 2?…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…4a. The peaks at 169.7, 781.7 and 855.07 eV, corresponds to S 2p, Co 2p and Ni 2p spectrums, respectively, indicating the existence of S, Co and Ni elements in the as-synthesized sample [19]. Figure 4b shows Co 2p spectrum, the Gaussian fitted peaks around binding energy of 781.931 and 797.677 eV shows the existence of Co 2?…”
Section: Resultsmentioning
confidence: 86%
“…and the peaks around binding energy of 779.063 and 795.268 eV corresponds to Co 3? , while the two remaining are satellite peaks of Co 2p spectrum [19,21]. Similarly, in Ni 2p spectrum Fig.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Additionally, the fabricated core-shelled NiCo 2 S 4 nanoarrays//AC asymmetric HSC device exhibits an energy density of 22.8 W h kg −1 at a power density of 160 W kg −1 . In another study, in contrast, www.advenergymat.de NiCo 2 S 4 nanotubes are decorated on NiCo 2 S 4 nanosheet arrays by a multistep method, [181] which can be clearly observed from Figure 4c [182] Copyright 2015, Royal Society of Chemistry. Panels (c,d): Reproduced with permission.…”
Section: Ni-co-smentioning
confidence: 99%
“…[70,[178][179][180][181][182] The hierarchically structured nanoarrays are expected to enlarge the utilization of the active materials, endowing more electroactive sites for ion adsorption and Faradaic redox reactions. For example, Kong et al reported the synthesis of a core-shelled hierarchical structure on NF, [182] in which NiCo 2 S 4 nanotubes are wrapped by NiCo 2 S 4 nanosheets, as shown in Figure 4a,b. They observed that the hydrothermal sulfidation temperature of 110 °C is essential to transform the nickel cobalt carbonate hydroxide nanowire precursor into core-shelled structure NiCo 2 S 4 .…”
Section: Ni-co-smentioning
confidence: 99%